(untitled) (Hoboken, N.J, 2012)
Microsoft insiders join giants of the software development community to offer this in-depth guide to ASP.NET MVC, an essential web development technology. Experienced .NET and ASP.NET developers will find all the important information they need to build dynamic, data-driven websites with ASP.NET and the newest release of Microsoft's Model-View-Controller technology. Featuring step-by-step guidance and lots of code samples, this guide gets you started and moves all the way to advanced topics, using plenty of examples.
Keywords: Web sites,Trang web,Microsoft .NET Framework